Shade of solar panels relieves heat load of sheep - Carvalho Fonsêca, Vinicius de França [UNESP]; de Andrade Culhari, Eric [UNESP]; Moura, Gustavo André Bernado [UNESP]; Nascimento, Sheila Tavares; Milan, Hugo Maia [UNESP]; Neto, Marcos Chiquitelli [UNESP]; Maia, Alex Sandro Campos [UNESP] (Elsevier, 2023)
Use of solar panels as shading resource combines better animal welfare, generation of renewable energy and animal production in the same area. This concept is termed Animal Agrivoltaics. In this study we integrated behavioural and physiological data in order to determine benefits provided by shade of solar panels on heat stress indicators of sheep. Nine adult Corriedale ewes (Body mass: 70 ± 12 kg; fleece length: 70 ± 5 mm) had miniature temperature loggers attached on them for every-minute samplings of wool-surface, skin and vaginal temperature, from 08:00 to 17:00 h, along 20 consecutive days. Ewes also had shade-use behaviour directly and continuously monitored. Ewes were kept in a paddock shaded with a roof structure that consists of ten photovoltaic panels (shade availability: 2.14 m2 animal−1). Over the study period, ewes were exposed to levels of solar radiation as much as 900 W m−2. From 08:00 to 17:00 h, regardless of the duration of sun exposure or in the shade of solar panels, the vaginal temperature of ewes remained within a narrow range (38.5 ºC - 39.2 ºC). At levels of solar irradiance above 500 W m−2, ewes increased wool-surface temperature by 10 ºC and skin temperature by 2 ºC with increasing heat load and time exposed to sun. Under such circumstances, they were more likely to move to shade of solar panels. Between 10:00 and 14:00 h, shade of solar panels provided to ewes 30 % less radiant heat load than if they were exposed to sun. As a result, as the time in shade increased, the wool-surface temperature of ewes was reduced by 7 ºC - 8 ºC, and skin temperature by 1.0 ºC - 1.5 ºC. In conclusion, this study provides strong evidence that shade of solar panels efficiently reduces heat load in sheep.
Keywords: Animal agrivoltaics; Shading; Thermal comfort; Thermoregulation